Some morphological aspects of Asian honey bee (Apis cerana) and isolation of its melittin content - Mumu, NN; Sarker, M; Islam, MR; Akand, S; Bashar, MA (Journal of Biodiversity Conservation and Bioresource Management, 2018)
Melittin is a major component of honey bee venom that has many biological effects including anticancer properties. The melittin content of Asian honey bee (Apis cerana F.) venom was isolated and quantify by reversed phase-high performance liquid chromatography (RP-HLPC) in Bangladesh. Melittin content was found to present in 59.3% of total venom content in Asian honey bee venom. Venom compounds were investigated at 254 nm and the retention time of venom-melittin was compared with an external standard (Sigma-Aldrich). This finding was compared with previously published findings. By comparing the present data with the earlier studied findings, a projection has been made on the quantification of melittin compound. J. Biodivers. Conserv. Bioresour. Manag. 2017, 3(2): 77-84